AQ-13 A Cross Sectional Survey Seroprevalensi of Antibody Present Against Salmonella Pullorum from Chicken in Banjarmasin Quarantine Services - Rima Hasmi Firdiati (Hemera Zoa, 2018)
Chicken is a poultry that is widely maintained in Indonesian society. From the village even up to a small portion of the city's population. Chicken Benefits derived from chicken and others for, household, and meat for other relief. Maintenance of many chickens by the customs and religious activities. Bringing the exploration done by the people here is something that can be done both between regions and between islands. It causes chicken or poultry traffic is very high in The Agricultural Quarantine Service (BKP) Class I of Banjarmasin. Before carrier, chicken or poultry must be healthy from various diseases. Pullorum is one of the most important diseases in chickens. Pullorum is a Quarantine Animal Disease Pest Group II (HPHK Gol. II) Regulation of the Minister of Agriculture [1] on Classification of Types of Quarantine Animal Diseases, Classification and Carrier Media Classification.                Pullorum is a disease in chickens caused by Salmonella pullorum bacteria. Form of S. pullorum bacteria in the form of short stems, gram negative, not spora and chicken as its specific host. Penile transmission can occur vertically through eggs and mothers to their children or horizontally by direct or indirect contact. It can be directly through drinking water, feed, cage equipment and indirectly through vectors or intermediary animals such as insects and rats [2]. Chicks, adult chickens, peacocks, canaries, turkeys and ostriches. Pullorum infection in mammals is very rare despite research reports or natural infection in rabbits, pigs, cats, cattle and mice [3].                Symptoms of pullorum disease include white defecation and in young chickens or poultry causing very high mortality, while in adult chickens act as a career [2]. The purpose of this paper to know the sero prevalences of the   pullorum disease and factors associated with the incidence of S. pullorum in chickens carried in The Agricultural Quarantine Service (BKP) Class I of Banjarmasin.